Relationship between precipitation and water-table fluctuation in a coastal dune aquifer: northeastern coast of the Buenos Aires province, Argentina - Carretero, Silvina Claudia (2012)
The water-table fluctuation (WTF) method is one of the most widely used means to estimate aquifer recharge. In the northeastern coast of the Buenos Aires province, Argentina, the geomorphological and climatic characteristics, as well as the presence of a shallow, homogeneous unconfined aquifer, make it possible to apply this methodology. The relationship between water-table fluctuations and precipitation in a humid climate, considering its seasonal variations, is assessed. Water tables were measured monthly between February 2008 and September 2010 in a monitoring network; rainfall data were analysed. The water table rises when the accumulated precipitation between measurements is more than 53 mm/month in the dry season and more than 97 mm/month in the rainy season. The index, relating water-table fluctuations and precipitation occurring between measurements, shows that values below 0 suggest no increase in the water reserves, whereas higher values entail an increase. In the study area, where there is a lack of historical data, finding out the relationship between water-table fluctuations and precipitation will constitute a tool for groundwater use and management, and set up an early warning system for dry periods. It could also be extrapolated to other regions with similar hydrological conditions lacking in data.